An Optimized Model for Solar Thermal Collectors Based on Concept of Effective Heat Collection. (June 2016) - Lv, Yuexia; Si, Pengfei; Liu, Xichen; Rong, Xiangyang; Feng, Ya; Yan, Jinyue
Abstract: The performance of solar collector highly relies on its tilt angle with respect to horizontal plane and orientation (surface azimuth angle) of the collector. The effective heat collection concept was proposed and an optimized mathematical model was further developed to determine the optimum tilt angle and orientation for the solar collector. The developed model was applied in a case study of the Lhasa district, in comparison with the results obtained in accordance with conventional optimization results. The research results showed that, there is about 5 deviation between the optimum results obtained according to effective heat collecting capacity and the optimum results obtained according to maximum total solar radiation falling on the solar collector.